Preventive effect of small molecule active substances on septic cardiomyopathy after abdominal trauma: a systematic review and meta-analysis - Ouyang, Gen; Wang, Neng; Liu, Yujuan; Yang, Chuang; Zeng, Peng; Gong, Tao; Tao, Lu; Zheng, Ying; Ye, Guiying; Li, Hong; Che, Chi; Wang, Longhai; et al. (Frontiers in Pharmacology, 2026)
ObjectiveThis systematic review and meta-analysis aimed to comprehensively evaluate the preventive effects and mechanisms of active small molecules against septic cardiomyopathy (SCM) induced by abdominal trauma or abdominal-origin sepsis in animal models.MethodsThe PubMed, Embase, Web of Science, Scopus and Cochrane Library databases were searched in January 2000- May 2025 for studies assessing active small molecules in animal SCM models. The standardised mean difference ([SMD], Hedges’ g) with 95% confidence intervals (CIs) was calculated using random-effects meta-analysis. Subgroup analyses were conducted according to molecular categories, sepsis induction methods, and outcome measures. Methodological quality was assessed using the Systematic Review of Laboratory Animal Experiments risk-of-bias tool.ResultsSeventeen studies met the inclusion criteria. The pooled meta-analysis showed that active small molecules had an overall beneficial but heterogeneous effect on SCM (SMD = 1.47, 95% confidence interval [CI]: −0.52–3.47, I2 = 92.9%). Subgroup analyses revealed large but imprecise effects for polyphenols (SMD = 4.81, 95% CI: −5.25–14.87) and neutral effects for flavonoids (SMD = −0.45, 95% CI: −3.64–2.73). The efficacy was greater in lipopolysaccharide-induced sepsis models (SMD = 2.86) compared with cecal ligation and puncture models (SMD = 0.16). Outcomes involving cardiac injury biomarkers (creatine kinase and creatine kinase isozymes) showed consistently positive and robust effects, while functional outcomes (e.g., left ventricular ejection fraction) exhibited inconsistent results. Sensitivity analyses confirmed robustness, while funnel plots indicated possible publication bias (Egger’s test, p = 0.123). Methodological limitations, including incomplete reporting of randomisation, blinding and allocation concealment, were commonly observed.ConclusionActive small molecules demonstrate generally positive yet heterogeneous preventive efficacy against SCM in animal models, with polyphenolic compounds in particular showing notable potential. Variability across molecular categories, sepsis models and measured outcomes highlights the need for standardised methodologies in future studies.